NILAI BUDAYA DALAM NAMA UPACARA ADAT MASYARAKAT BETAWI - Neneng Nurjanah; Dwi Agustin (Universitas Sultan Ageng Tirtayasa, 2023)
This study aims to examine the cultural values contained in the names of Betawi traditional ceremonies. This research uses qualitative descriptive methods with the type of documentation. The data in this study, namely the cultural lexicon related to the names of Betawi traditional ceremonies. Data collection techniques in this study are interviews, observations, and documents. As for the findings of this study, namely the cultural values contained in the Betawi traditional ceremony contain the most cultural values that are related and oriented to human relations, among the 19 names of traditional ceremonies, nine ceremonies were found, namely puput puser, selametan ngasih nama, malem mangkat, ijab kabul, tepak dangdang, sungkem, duduk di taman pengantèn, selametan tiga ari and sedekahan ngawinin.